Adapted CBT to Stabilize Sleep on Psychiatric Wards: a Transdiagnostic Treatment Approach. Issue 6 (4th April 2018) - Sheaves, Bryony; Isham, Louise; Bradley, Jonathan; Espie, Colin; Barrera, Alvaro; Waite, Felicity; Harvey, Allison G.; Attard, Caroline; Freeman, Daniel
Abstract : Background: Almost all patients admitted at acute crisis to a psychiatric ward experience clinically significant symptoms of insomnia. Ward environments pose challenges to both sleep and the delivery of therapy. Despite this, there is no description of how to adapt cognitive behavioural therapy (CBT) for insomnia to overcome these challenges.Aims: (i) To describe the key insomnia presentations observed in the Oxford Ward Sleep Solution (OWLS) trial and (ii) outline key adaptations aimed to increase accessibility and hence effectiveness of CBT for insomnia for a ward setting.Methods: Trial therapists collaboratively agreed the key insomnia presentations and therapy adaptations based on their individual reflective logs used during the trial.Results: Three key insomnia presentations are outlined. These are used to illustrate the application of 10 CBT for insomnia therapy adaptations. These include use of sleep monitoring watches to engage patients in treatment, stabilizing circadian rhythms, reducing the impact of night-time observations and managing discharge as a sleep challenge.Conclusions : Whilst inpatient wards bring challenges for sleep and therapy delivery, creative adaptations can increase the accessibility of evidence based CBT for insomnia techniques. This therapy has proven popular with patients.